Can anyone plz help me out with this question ?
Attachments:
![](https://hi-static.z-dn.net/files/db3/203baca3f720b33306dce270279f8251.jpg)
Answers
Answered by
1
=(3+√3)[ (2+√2)²]
use formula (a+b)²= a²+b²+2ab
=(3+√3) [4+2(2)(√2)+2]
=(3+√3) [6+4√2]
=3(6+4√2)+√3(6+4√2)
=18+12√2+6√3+4√6
use formula (a+b)²= a²+b²+2ab
=(3+√3) [4+2(2)(√2)+2]
=(3+√3) [6+4√2]
=3(6+4√2)+√3(6+4√2)
=18+12√2+6√3+4√6
Similar questions
Math,
9 months ago
Hindi,
9 months ago
Computer Science,
9 months ago
Math,
1 year ago
Social Sciences,
1 year ago